Complementarity of labor market institutions, equilibrium unemployment and the persistence of business cycles - Michael C. Burda; Mark Weder (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
This paper evaluates complementarities of labor market institutions and the business cycle in the context of a stochastic dynamic general equililbriurn model econorny. Matching between workers and vacancies with endogenous search intensity, Nash-bargained wages, payroll taxation, and differential support for unemployed labor in search and leisure are central aspects of the model. For plausible regions of the policy and institutional parameter space, the model exhibits more persistence than standard RBC models and often indeterminacy of rational expectations paths without increasing returns in production. Furtherrnore~ labor rnarket institutions act in a complementary fashion in generating these effects.
urn:nbn:de:kobv:11-10046404
Keywords: 330